Formation of the Architectural Environment of Canals in the City of Fergana - Jo‘rayev O‘ktamjon Shavkatovich; Orifjonov Islombek Umidjon ogli (Genius Journals, 2022)
A total of 42 km of canals in the city area have been inspected by a specially established commission, and the sanitary condition of canals and water management structures, 7.5 km along Margilonsoy is currently under repair. The channel is fenced with special railings and decorated with coloured stones. This is mainly the result of the works carried out along the Margilonsoy canal. It was found that the strength of the shores of the existing 1.5 km canal along the Akhunboboev basin, and the level of beautification of the areas along the canal is in an unsatisfactory condition, which has a negative effect on the appearance of the city.
Keywords: Water management facilities; sanitation; Margilonsoy canal; landscaping